A comprehensive study on structure, opto-nonlinear and photoluminescence properties of Co3O4 nanostructured thin films: An effect of Gd doping concentrations. Issue 10 (15th May 2022) - Shkir, Mohd; Khan, Z.R.; Khan, Aslam; Chandekar, Kamlesh V.; Sayed, M.A.; AlFaify, S.
Abstract: Cobalt oxide (Co3 O4 ) thin films with 0, 1.0, 3.0 and 5.0 wt% Gd doping concentrations were fabricated on glass substrates by spray pyrolysis method. X-ray diffraction pattern (XRD) of as-deposited thin films confirm spinel structure growth oriented along (311) plane. Crystallite sizes of the grown films decreases with the increase in Gd doping concentrations and found in range of ∼17.7–7.2 nm. Raman investigation of films further approves spinel growth of cobalt oxide films. Surface morphology of pure and Gd: Co3 O4 thin films were analyzed using field emission scanning electron microscopy (FESEM) with round shape particles at nanoscale. Chemical compositions, elements, and their stoichiometry were observed by energy dispersive spectra (EDX). Tauc's plots of films clearly shows two direct optical band gaps, (1) in the range of 1.49–1.52 eV and (2) in the range of 2.01 eV–2.58 eV respectively. A significant impact of Gd doping was observed on second optical band gaps, which increases with Gd contents. Room temperature (RT) dependent photoluminescence (PL) spectra of the deposited films showed that emission peaks at 363, and 753 nm under excitation wavelength of 240 and 500 nm respectively. The third order nonlinear optical susceptibility χ (3) and nonlinear refractive n (2) which were calculated and found in range 4.46 × 10 −13 - 2.25 × 10 −10  esu and 1.01 × 10 −10 -2.39 × 10 −9  esu., respectively.